2024
DOI: 10.1101/2024.03.12.584660
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reliability of brain metrics derived from a Time-Domain Functional Near-Infrared Spectroscopy System

Julien Dubois,
Ryan M. Field,
Sami Jawhar
et al.

Abstract: With the growing interest in establishing brain-based biomarkers for precision medicine, there is a need for noninvasive, scalable neuroimaging devices that yield valid and reliable metrics. Kernel's second-generation Flow2 Time-Domain Functional Near-Infrared Spectroscopy (TD-fNIRS) system meets the requirements of noninvasive and scalable neuroimaging, and uses a validated modality to measure brain function. In this work, we investigate the test-retest reliability (TRR) of a set of metrics derived from the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Further, those channels that exhibited the most statistically significant responses to task conditions revealed strong task-locked modulations. It is worth noting that we previously demonstrated the stability of such task-evoked metrics in a larger-scale study with the Flow2 device ( 34 ). Taken together, these findings uphold the two pillars of device performance for research and clinical-use: validity and reliability.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Further, those channels that exhibited the most statistically significant responses to task conditions revealed strong task-locked modulations. It is worth noting that we previously demonstrated the stability of such task-evoked metrics in a larger-scale study with the Flow2 device ( 34 ). Taken together, these findings uphold the two pillars of device performance for research and clinical-use: validity and reliability.…”
Section: Discussionmentioning
confidence: 72%
“…Additionally, as with other optical neuroimaging devices, hair can limit signal quality, as it absorbs light which reduces signal at the detectors. We have found that at least 1000 usable channels are available over the head for most participants ( 34 ) there is still room for improvement in mechanical design to ensure good optical coupling by working through all hair types and making contact with the scalp at all locations. Moreover, as with all diffuse optical systems, deep brain structures remain inaccessible.…”
Section: Discussionmentioning
confidence: 99%